Tgx=tg2x sin2x-2корня из 3cos^2x=0 cos^2(pi-x)-2cosx=0 cos4x+cosx=0 2sin^2(3pi/2)-3sin(pi/2+x)-2=0 1-cos2x=sinx Срочно 100 баллов

Tgx=tg2x sin2x-2корня из 3cos^2x=0 cos^2(pi-x)-2cosx=0 cos4x+cosx=0 2sin^2(3pi/2)-3sin(pi/2+x)-2=0 1-cos2x=sinx Срочно 100 баллов
Гость
Ответ(ы) на вопрос:
Гость
1 tgx=2tgx/(1-tg²x) {tgx-tg³x-2tgx=0⇒tg³x+tgx=0⇒tgx(tg²x+1)=0⇒tgx=0⇒x=πn,n∈z (tg²x+1>0) {1-tg²x≠0 Ответ x=πn,n∈z 2 2sinxcosx-2√3cos²x=0 2cosx(sinx-√3cosx)=0 cosx=0⇒x=π/2+πn,n∈z sinx-√3cosx=0/cosx⇒tgx-√3=0⇒tgx=√3⇒x=π/3+πn,n∈z 3 sin²x-2cosx=0 1-cos²x-2cosx=0 cosx=a a²+2a-1=0 D=4+4=8 a1=(-2-2√2)/2=-1-√2⇒cosx=-1-⇒2<-1 нет решения a2=-1+√2⇒cosx=√2-1⇒x=+-arccos(√2-1)+2πn,n∈z 4 2cos(5x/2)*cos(3x/2)=0 cos(5x/2)=0⇒5x/2=π/2+πn⇒x=π/5+2πn/5,n∈z cos(3x/2)=0⇒3x/2=π/2+πn⇒x=π/3+2πn/3,n∈z 5 2*1-3cosx-2=0 -3cosx=0 cosx=0 x=π/2+πn,n∈z 6 2sin²x-sinx=0 sinx(2sinx-1)=0 sinx=0⇒x=πn,n∈z sinx=1/2⇒x=(-1)^n*π/6+πn,n∈z
Не нашли ответ?
Ответить на вопрос
Похожие вопросы